Environmental-Based Tourism Village Modeling in Tasikmalaya District, West Java - Siti Fadjarajani; Sunaedi, Nedi; Erni Mulyanie; Hilman Hakim, Erwin (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
The tourism sector in Tasikmalaya Regency has very good potential to be developed towards an ecotourism-based tourism area. The objectives of this study were: to identify the level of fulfillment of the criteria for a tourist village in Santana Mekar Village, Tasikmalaya; and formulate the development and modeling of environmentally-based tourism villages. The research method used is a qualitative research method with a field survey. Analysis of the potential of the three tourist areas using SWOT analysis. Santana Mekar Village has tourism potential which can be divided into three categories, namely: natural tourism, educational tourism, and cultural tourism, based on these three potentials, Santanamekar village can be used as a model for eco-based tourism village and become leading tourism in Tasikmalaya Regency. The results of this study are expected to provide important information about tourism potential that can be developed and can be input for local governments in tourism development policies in Tasikmalaya Regency.